Kualitas Pelayanan BPJS Pada Klinik Di Kota Pekanbaru - Hadiyati, Hadiyati (Komunitas Manajemen Kompetitif, 2015)
Abstract: Abstract: Ministry of Social Security Agency (BPJS) is the Social Security Agency established by the government to provide for Public Health Insurance, National Health Insurance (JKN) is a public health program to realize the health services in accordance with medical needs. BPJS Health Care not for all Indonesian people. Public complaints against the service based on the results of the study proved to be due for service procedures that are less well applied and also because of the service provided is not using the right people and facilities are also incomplete, although the specified low cost but not efficient in making the community recover of the disease. Keywords: Quality of Service, BPJS